SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN PUCUK MENGGUNAKAN METODE AHP BERBASIS WEB - Ubaidilla Maghfur; M Hasan Wahyudi (Jurnal Teknika, 2018)
Decision  Support  System  is  Information  management  aids  system  that  deals  with  the  calculation  and  assessment  of  employees  in  sub-district  service,  many  ways  to  assess  employee  performance but this system that I created, as in advance company this system is often in use. In this  research using AHP method. Making this performance appraisal decision support system using a  web system. The system  was created can provide an appraisal to assess the  work of employees in  PATENT